Cerebral Pressure Passivity in Newborns with Encephalopathy Undergoing Therapeutic Hypothermia - Govindan, Rathinaswamy Bhavanandhan; Massaro, An N.; Andescavage, Nickie N.; Chang, Taeun; du Plessis, Adré (Frontiers in Human Neuroscience, 2014)
We extended our recent modification of the power spectral estimation approach to quantify spectral coherence. We tested both the standard and the modified approaches on simulated data which showed that the modified approach was highly specific and sensitive to the coupling introduced in the simulation while the standard approach lacked these features. We also applied the modified and standard approaches to quantify the pressure passivity in 4 infants receiving therapeutic hypothermia. This was done by measuring the coupling between continuous cerebral hemoglobin differences and mean arterial blood pressure. Our results showed that the modified approach identified a lower pressure passivity index (PPI, percent time the coherence was above a predefined threshold) than the standard approach ($P=0.0027)$.